Perkembangan Demokrasi di Amerika Serikat: dari Revolusi hingga Era Modern - Putri, Shella Ananda; Safitri, Fivie; SM, Indah Chofifah; Ananda, Risky Dwi; Andira, Bagas Ibnu; Zalukhu, Deveronika; Zai, Diraningsih (Polyscopia, 2024)
This article examines the development of democracy in the United States from the American Revolution to the modern era, focusing on institutional, social, and political transformations over more than two centuries. Beginning with the Declaration of Independence and the creation of the Constitution, it explains how democratic principles were established and tested through challenges such as the Civil War, the civil rights movement, and economic and technological changes. Through historical and critical analysis, the article explores the evolution of voting rights, public participation, and power dynamics at federal and state levels. Additionally, it highlights the role of individuals and groups in shaping democratic structures and the impact of domestic and international policies on American democracy. The findings show significant progress, but ongoing challenges to democratic principles include political polarization, economic inequality, and threats to civil rights. In conclusion, the article emphasizes understanding the history of American democracy to address contemporary challenges and strengthen commitment to democratic values.